Analysis of Farmer's Perception and Constraints on Dairy Cooperatives in Amhara Region, Ethiopia - Molla, Abateneh; Abebe, Azanaw; Balew, Mulugeta; Assefa, Desyalew; Kehali, Senait (Food, Agriculture and Natural Resources - NETWORKS, 2024)
This study was done to examine the farmer’s perception and constraints on dairy cooperatives in Amhara region, Ethiopia. A sample of 266 smallholder dairy farmers was selected using a multi-stage sampling technique. Perception of farmers was analyzed using relative importance index, and constraints of dairy cooperative performance were analyzed using Henry Garrett's ranking technique. The result indicates that farmers have a positive perception of certain attributes of dairy cooperatives; such as increasing social networks, improving income, and serving as a saving source. This suggests that farmers believe these aspects of dairy cooperatives are beneficial. Conversely, farmers have concerns and dissatisfaction with the way the cooperative is running, the loyalty of members to the cooperative, member's treatment by cooperatives, and the decision-making process. The study also identified that lack of milk processing facilities, poor member awareness, and member involvement in the decision-making process are the foremost internal challenges of dairy cooperatives, while high cost of cross-breed cows, occurrence of animal disease, and low productivity of local breed cows are external constraints hindering dairy cooperative performance. Thus, to enhance farmers' perception and participation in cooperative activities, emphasis should be given to addressing concerns and improving the overall functioning of dairy cooperatives.